The innovation revealed by the extensive margin in the exports of the suppliers of mining services in Chile - Cordero Espinosa, Carlos Sebastián (2018)
The Chilean mining industry provides a great contribution to the exports and the economic growth of this country. The innovation of the mining industry is key to improve the productivity, cut costs, reduce negative environmental externalities, and diversify the exports. These challenges constitute an opportunity for companies providers of services in mining, because being involved in the creation of knowledge-intensive solutions, contributes to the diversification of the export basket of this sector and the solution of environmental challenges. In this article, innovation is analyzed through export diversification, classifying the exports’ variations in intensive and extensive margins. The latter is interpreted as indirect evidence of innovation in exports, represented by the entry of new combinations of companies, types of services and destination markets. Within the extensive margin, companies are differentiated by their capital’s origin, being Chilean or foreign owned. The results indicate that Chilean companies have a much more important role in the diversification and innovation of the sector, compared to their modest participation in exports.